More Than Moore Technologies for Next Generation Computer Design 2015
DOI: 10.1007/978-1-4939-2163-8_6
|View full text |Cite
|
Sign up to set email alerts
|

Main Memory Scaling: Challenges and Solution Directions

Abstract: The memory system is a fundamental performance and energy bottleneck in almost all computing systems. Recent system design, application, and technology trends that require more capacity, bandwidth, efficiency, and predictability out of the memory system make it an even more important system bottleneck. At the same time, DRAM technology is experiencing difficult technology scaling challenges that make the maintenance and enhancement of its capacity, energy-efficiency, and reliability significantly more costly w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 99 publications
(107 reference statements)
0
9
0
Order By: Relevance
“…Today's emerging data-intensive applications and systems in domains such as AI, cloud, and HPC continue to demand greater memory capacity at an unprecedented scale [173][174][175][176][177]. Unfortunately, technology shrinkage throughout the past two decades has yielded diminishing benefits for chip storage capacity, access latency, and refresh overheads because of the growing costs and overheads of maintaining reliable chip operation at smaller technology node sizes [10,11].…”
Section: Slowdown Of Generational Improvementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Today's emerging data-intensive applications and systems in domains such as AI, cloud, and HPC continue to demand greater memory capacity at an unprecedented scale [173][174][175][176][177]. Unfortunately, technology shrinkage throughout the past two decades has yielded diminishing benefits for chip storage capacity, access latency, and refresh overheads because of the growing costs and overheads of maintaining reliable chip operation at smaller technology node sizes [10,11].…”
Section: Slowdown Of Generational Improvementsmentioning
confidence: 99%
“…First, improvements to DRAM access latency and storage capacity are slowing down due to DRAM technology scaling challenges [10,11]. To illustrate this problem, we survey 58 publicly-available DRAM chip datasheets 1 in Section 3.1, broadly sampling chips from across 19 DRAM manufacturers spanning the past five decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study showed that given the number of cores increasing faster than DRAM capacity, the expected memory capacity per core would decrease by 30% every two years (Mutlu & Subramanian, 2015). When scaling the size of the computing system, memory also must be scaled, but this makes the maintenance and enhancement of its capacity, energy efficiency, and reliability significantly costlier than conventional techniques (Mutlu, 2015). RH attacks are about the idea that hardware is not so vulnerable and one can attack hardware by exploiting its vulnerabilities.…”
Section: Rowhammer (Rh) Vulnerabilitymentioning
confidence: 99%
“…The growth in the required data for complex applications and an increase in the number of cores on a single chip lead to high demands for memory capacity and bandwidth [1, 2]. To mitigate the speed gap between processor and off‐chip memory, it is indispensable to exploit large, multi‐level, on‐chip cache hierarchy [3].…”
Section: Introductionmentioning
confidence: 99%